Hypoplasia of Extrahepatic Biliary Tree and Intrahepatic Cholangiolopathy in Cystic Fibrosis Imperfectly Mimic Biliary Atresia in 4 Infants With Cystic Fibrosis and Kasai Portoenterostomy. (13th November 2021) - Bove, Kevin E.; Bernieh, Anas; Picarsic, Jennifer; Cox, Joseph P.; Yang, Edmund; Mantor, Philip C.; Thaker, Ameet; Lazar, Lauren; Sathe, Meghana; Megison, Stephen
Abstract : Four male infants with cystic fibrosis and prolonged neonatal jaundice underwent Kasai procedure to relieve biliary obstruction due to apparent biliary atresia. The excised remnants had viscid mucus accumulation in hypoplastic gallbladders and distended peribiliary glands. Main hepatic ducts were narrow and/or malformed. Microscopic differences between the gallbladder and extrahepatic bile ducts in cystic fibrosis and sporadic biliary atresia were unequivocal, despite some histologic overlap; no erosive or fibro-obliterative lesions typical of biliary atresia were seen. Common in liver, biopsies were small duct cholangiopathy with intense focal cholangiolitis and massive accumulation of ceroid pigment within damaged cholangiocytes, and in portal macrophages, portal fibrosis, and unequivocal features of large duct obstruction were inconspicuous compared with biliary atresia. Plugs of bile in small ducts tended to be pale and strongly periodic acid–Schiff-reactive in cystic fibrosis. Distinguishing the liver lesion from that of biliary atresia is challenging but possible. Liver biopsies from 2 additional infants with cystic fibrosis and prolonged jaundice that spontaneously resolved showed a similar small duct cholangiopathy. Small gallbladders and extrahepatic ducts challenge surgical judgment as findings in liver biopsies challenge the pathologist. The decision to perform a Kasai procedure is reasonable when mimicry of biliary atresia is grossly complete. We hypothesize that a disorder of bile volume/flow during development and/or early infancy linked to the CFTR mutation alone or in combination with the stresses of neonatal intensive care causes destructive cholangiolitis and intrahepatic reduction of bile flow with secondary hypoplasia of extrahepatic biliary structures.